Transesterification of biodiesel from kapok seed oil (ceiba pentandra) using a natural heterogeneous katalyst (rice husk activation) - ., Marhaini; Sri Yusmartini , Eka; Okka Widhanny , Larasati (International Journal of Advanced Chemistry, 2024)
Biodiesel as a renewable energy source can be produced by a chemical reaction between vegetable oil or animal fat and short-chain alcohol such as methanol, ethanol or buthanol and is supported by a catalyst. This process is called transesterification. From an environmental point of view, the use of biodiesel has several advantages such as reducing carbon dioxide emissions, being non-toxic and biodegradable. Kapok seed oil has potential for exploitation, particularly as a raw material for the manufacture of biofuel. Kapok seeds (Ceiba pentandra) have the potential to be used as a feedstock for biodiesel because their oil content is quite high, around 18-25% oil. The controlled combustion of rice husks produces ash containing high purity amorphous silica. Amorphous silica can be obtained from RHA (rice husk ash) when rice husk is burned at a temperature of 700°C, and it is transformed into crystalline silica when burned at a temperature above 850 °C. This silica has many applications as a filler, adsorbent, catalyst support, star gel component and source for the production of premium silicon and its compounds. The aim of the research is to determine the transisterification process of biodiesel from kapok (Ceiba pentandra) seed oil. using a natural heterogeneous catalyst in It is an activated rice husk. The method used was the preparation of kapok seed samples and the extraction of sokhlet. Determination of free fatty acids (FFA) in kapok seed oil, activation of rice husk, manufacturing of biodiesel from kapok seed with addition of rice husk H2SO4 as catalyst. The characteristics of the biodiesel produced are Density: 859.88572 kg/m3 (SNI: 7182:2015) = 850-890 kg/m3), Viscosity: 2.45824 cSt (SNI: 7182:2015) = 2.3 – 6, 0 cSt, Calorific value: 7,374.5322 cal/g (SNI: 7182; 2015) = 7,100 -11,000 cal/ g, Devil's number: 48 (ASTM: D6751) = 47. Meanwhile, GC-MS with the highest values at all reaction times, namely Hexadec anoic acid, methyl ester (C17H34O2), methyl tetradecanoate (C15H30O2) and 9 - Octadecenoic acid (Z), methyl ester (C19H36O2) . The functional group found in kapok seeds is –OH.